2015
DOI: 10.1111/liv.12889
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological indices to predict hepatocellular carcinoma molecular classification

Abstract: Background & Aims Hepatocellular carcinoma (HCC) is the second most lethal cancer due to lack of effective therapies. Although promising, HCC molecular classification, which enriches potential responders to specific therapies, has not yet been assessed in clinical trials of anti-HCC drugs. We aimed to overcome these challenges by developing clinicopathological surrogate indices of HCC molecular classification. Methods HCC classification defined in our previous transcriptome meta-analysis (S1, S2, and S3 subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 56 publications
(78 reference statements)
4
102
1
Order By: Relevance
“…In conclusion, in the present autopsy cohort we found relevant associations between immunohistochemical markers with morphological features of tumors, especially that of histological grading of HCC [35] . The expression of K19, p53, ERK1, ERK2, vimentin and nuclear beta-catenin showed an association with pathological markers of higher-grade tumors, as opposed to cases expressing/over-expressing EGFR, MET and caspase 3.…”
Section: Discussionmentioning
confidence: 72%
“…In conclusion, in the present autopsy cohort we found relevant associations between immunohistochemical markers with morphological features of tumors, especially that of histological grading of HCC [35] . The expression of K19, p53, ERK1, ERK2, vimentin and nuclear beta-catenin showed an association with pathological markers of higher-grade tumors, as opposed to cases expressing/over-expressing EGFR, MET and caspase 3.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, HCCs with a macrotrabecular pattern were also reported to belong to the S2 signature subclass described by Hoshida and colleagues [18,34], and were correlated with the activation of the YAP oncogene and with the expression of the stemness markers K19 and EpCAM. Moreover, macrotrabecular-massive HCCs were found to belong to the G3 signature subclass described by Boyault et al [34], which is known to be an aggressive molecular subtype of HCC, and were correlated with poor survival, vascular invasion, TP53 mutation, and FGF19 amplification [19,34].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been found to be involved in the maintenance of cancer stem cells, which are characterized by their ability to self-renew and propagate tumors, and play an important role in tumor maintenance and recurrence [32,33]. HCCs expressing stemness markers, such as K19 and EpCAM, are reportedly associated with poor prognosis and molecular signatures of aggressive biological behavior such as S2 (Hoshida et al [34]) and G1 (Boyault et al [35]) compared to HCCs that do not express these markers [18,19,[34][35][36][37][38]. Rhee et al [23] also recently reported a close association between the expression of the hypoxia marker CAIX and stemness markers including K19 and EpCAM in HCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TERT activation is most frequently and commonly seen across etiologies despite the wide variety of molecular alterations leading to the pathway activation such as HBV integration, genomic DNA amplification or promoter mutation [61]. Interestingly, the S2 subclass (common theme #2) is relatively more frequent in HBV-related HCC – also less associated with cirrhosis – suggesting that HBV genomic integration leads to enrichment of this molecular subclass and supporting the presence of etiology-specific bias in the affected pathways [57,62–66]. …”
Section: Genome-based Molecular Classification Of Hccmentioning
confidence: 99%